Animals and their Relation to Gods, Humans and Things in the Ancient World
XII, 487 p. 1 illus.
Keywords: While Human-Animal Studies is a rapidly growing field in modern history, studies on this topic that focus on the Ancient World are few. The present volume aims at closing this gap. It investigates the relation between humans, animals, gods, and things with a special focus on the structure of these categories. An improved understanding of the ancient categories themselves is a precondition for any investigation into the relation between them. The focus of the volume lies on the Ancient Near East, but it also provides studies on Ancient Greece, Asia Minor, Mesoamerica, the Far East, and Arabia. Contents Human-Animal-Studies - Bridging the Lacuna between Academia and Society.- Reflections on the Pivotal Role of Animals in Early Mesopotamia.- Holy Cow! On Cattle Metaphores in Sumerian Literary Texts.- On Men, Animals, and Supernatural Beings in Ancient Maya Iconography. - Animal Friezes in "Orientalizing" Greek Art. Target Groups Lecturers, students andspecialists in the humanities and social sciences The Editors Dr. Raija Mattila is Docent of Assyriology, University of Helsinki, Finland, and Director of the Finnish Institute in the Middle East, Beirut, Lebanon. Dr. Sanae Ito is a historian and Research Fellow of Japan Society for the Promotion of Science. Dr. Sebastian Fink is Postdoctoral Researcher at the Academy of Finland Centre of Excellence “Changes in Sacred Texts and Traditions”. .